2009
DOI: 10.1002/app.29753
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of poly (MAA)‐crosslinked pregelled starch graft copolymer and its application in waste water treatments

Abstract: Propelled starch (PG) was first crosslinked with epichlorohydrin to obtain insoluble crosslinked pregelled starch (CPS). The latter was graft copolymerized with different amounts of Methacrylic acid using potassium persulphate as initiator. This was done to obtain six levels of poly (MAA)-crosslinked pregelled starch graft copolymers (PMCPS) having different graft yields (expressed as meq COOH/100 g starch) with increasing order and designated as (PMCPS 1 to PMCPS 6). The latter copolymers were dispersed in aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Initiator ceric ammonium nitrate (CAN) is widely used in the grafting of vinyl monomer onto starch because of some advantages such as the simple mechanism of single electron transfer, formation of free radicals on the backbone polymer itself, production of pure graft copolymer, and ease of application at an ambient temperature in aqueous medium 14. There are many reports on starch‐grafted vinyl copolymers, such as starch‐ g ‐poly(methacrylic acid), starch‐ g ‐polystyrene, starch‐ g ‐polyacrylonitrile, starch‐ g ‐polymethacrylonitrile, and starch‐ g ‐polyacrylamide 15–19. Most of reports focused on the influence of reaction time, temperature, concentration of starch, vinyl monomer, and initiator on the GE and GP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initiator ceric ammonium nitrate (CAN) is widely used in the grafting of vinyl monomer onto starch because of some advantages such as the simple mechanism of single electron transfer, formation of free radicals on the backbone polymer itself, production of pure graft copolymer, and ease of application at an ambient temperature in aqueous medium 14. There are many reports on starch‐grafted vinyl copolymers, such as starch‐ g ‐poly(methacrylic acid), starch‐ g ‐polystyrene, starch‐ g ‐polyacrylonitrile, starch‐ g ‐polymethacrylonitrile, and starch‐ g ‐polyacrylamide 15–19. Most of reports focused on the influence of reaction time, temperature, concentration of starch, vinyl monomer, and initiator on the GE and GP.…”
Section: Introductionmentioning
confidence: 99%
“…14 There are many reports on starch-grafted vinyl copolymers, such as starch-g-poly(methacrylic acid), starch-g-polystyrene, starch-g-polyacrylonitrile, starch-g-polymethacrylonitrile, and starch-g-polyacrylamide. [15][16][17][18][19] Most of reports focused on the influence of reaction time, temperature, concentration of starch, vinyl monomer, and initiator on the GE and GP. Still now, there are few investigations on the correlation of GP to various properties such as morphology, thermal stability, crystallization behavior, and biodegradability.…”
Section: Introductionmentioning
confidence: 99%
“…carrier matrix became important [13][14][15][16][17][18]. Chelating polymers have also been produced and used as adsorbents for removal of toxic heavy metal ions in recent years [1,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. These selective polymeric adsorbents have gained a growing interest since they are especially useful in the removal of heavy metal ions from waste water effluents and reuse of the adsorbent polymer and recovery of heavy metals are also possible.…”
Section: Introductionmentioning
confidence: 99%
“…Removal of hexavalent chromium from tannery effluent Recently, a great deal of attention has been paid to develop cheaper and effective adsorbents containing natural polymers to overcome the non-biodegradability and high cost of the adsorbent resins. Among these, polysaccharides, such as chitin and chitosan (Ravi Kumar, 2000) cyclodextrin (Crini and Morcellet, 2002) as well as starch derivatives (Wurzburg, 1986) and (Mostafa et al, 2009) have shown their ability to remove heavy metal ions and dyes from aqueous solutions.…”
Section: Uv-visible Spectroscopymentioning
confidence: 99%